Capecitabine-induced Cardiotoxicity Complicated with Acute Coronary Syndrome and Acute Heart Failure: A Case Report and Review of Scientific Data - Mitevska, Irena; Kotlar Velkova, Irina; Grueva Nastevska, Elena; Shehu, Enes; Petkovski, Dushan; Chelikikj, Ana; Kandic, Elma; Otljanski, Matej; Papestiev, Vasil (Medicinska Naklada d.o.o., 2025)
Capecitabine cardiotoxicity is relatively common and may lead to serios cardiovascular complications. The aim of this case report is to emphasize the importance of considering potential toxic effects, rapid therapy discontinuation, and prompt treatment of all complications. We present a case of a 46-yearold male patient who was admitted to our clinic with chest pain and ST segment elevation in the anterior and lateral leads as a sign of acute ST-segment elevation myocardial infarction. Urgent coronary angiography was performed with the finding of a thrombus in the left anterior descendent coronary artery, and percutaneous coronary intervention was subsequently performed. Two months before admission, the patient had undergone surgery for rectal cancer. The above symptoms started three days after the introduction of treatment with capecitabine, which was discontinued on admission. The patient clinically deteriorated during the procedure, with development of cardiogenic shock. An echocardiography exam performed after the procedure showed severe reduction of left ventricular (LV) function (ejection fraction (EF) 21%). Due to further deterioration and cardiogenic shock refractory to optimal inotropic and vasopressor support, veno-arterial extracorporeal membrane oxygenation support was applied and the patient was placed on mechanical ventilation. After all these treatment measures, the patient clinically stabilized. He was extubated after 2 days and hemodynamically stabilized with gradually improvement of LV function. Control echocardiography after 9 days from admission showed an EF of 58%. Our case is an example of successful treatment of the potential serious cardiotoxic complications of capecitabine therapy in a young patient. The case also emphasizes the necessity of multidisciplinary collaboration in similar clinical scenarios.
Keywords: capecitabine; cardiotoxicity; heart failure; ST-segment elevation myocardial infarction